2022
DOI: 10.1158/1538-7755.disp21-pr-05
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PR-05: Worsening disparities of racial minority participation in phase 1 early drug development trials in the United States, 2001-2018

Abstract: Purpose: The National Institute of Health has advocated for broad representation of racial and ethnic groups in drug development trials after the introduction of the Revitalization Act in 1993. However, no studies to date have specifically examined demographic disparities among participants in Phase 1 drug development trials. Herein we sought to assess the distribution of and changes in enrollment of racial and ethnic minorities in United States Phase 1 early drug trials for metastatic cancer treatment from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Despite the unknowns, the current lack of diversity in EPCTs is clear. EPCTs under-represent women, 13 older adults, 14–16 those with lower education levels, 17 those who live further away from hospitals, 17 those from deprived areas, 18 ethnic minorities 19 20 and, for those studies undertaken in majority English-speaking societies, individuals with limited English proficiency. 21 It has been shown that participants experiencing socioeconomic deprivation have worse outcomes in cancer trials than those not experiencing socioeconomic deprivation 22 ; however, we do not know if this is the case for EPCTs due to the lack of data on diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the unknowns, the current lack of diversity in EPCTs is clear. EPCTs under-represent women, 13 older adults, 14–16 those with lower education levels, 17 those who live further away from hospitals, 17 those from deprived areas, 18 ethnic minorities 19 20 and, for those studies undertaken in majority English-speaking societies, individuals with limited English proficiency. 21 It has been shown that participants experiencing socioeconomic deprivation have worse outcomes in cancer trials than those not experiencing socioeconomic deprivation 22 ; however, we do not know if this is the case for EPCTs due to the lack of data on diversity.…”
Section: Introductionmentioning
confidence: 99%